Forces Perspective of Drillability of Titanium Alloy 6Al-2Sn-4Zr-6Mo - Mahros Darsin; Timotius Pasang; Zhan Chen (University of Muhammadiyah Malang, 2018)
This paper concerns on drillability of Ti-6Al-2Sn-4Zr-6Mo (Ti-6246) from the point view of thrust force (Fz) & torque (Mz) using a TiAlN CVD coated carbide tool. The condition of the material was varied with three different heat treatments. Whereas, the machining parameters were varied in cutting speed, feed rate and cooling application method. Taguchi method L-18 was employed to design the experiments. Both type of forces, thrust force and torque, were measured using a Kistler dynamometer, and the data were analyzed using a Minitab 17 software. The thrust force was influenced by the cutting speed 24%, depth of drilling 21%, heat treatment 13%, and feed rate 11%. The torque was influenced predominantly by feed rate up to 94%. Coolant application has no effect on reducing both thrust force as well as torque.